15e. sonate en ré majeur pour piano par Beethoven. Op. 28 ... - Beethoven, Ludwig van, 1770-1827 (composer):::Creator:::::::::::: (Schonenberger; Paris; France, 2022)
Edition of the Piano Sonata no. 15 in D major, op. 28, published as an "Edition correcte et à bon marché" in octavo format as Livraison 21 in the series, "Les classiques du piano" by Schonenberger in Paris.